UJI BAKTERI Bacillus sp. ENDOFIT DIFORMULASI DENGAN BEBERAPA LIMBAH TERHADAP TANAMAN PADI SAWAH (Oryza sativa L.) - Dini Oktrisna; Fifi Puspita; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The productivity of paddy which decreased influenced by high fertilizer requirements, while the price of inorganic fertilizers more expensive. Alternatif used to obtain an environmentally frriendly fertilization by using endophytic Bacillus sp. bacteria in the form of formulations, so that the Bacillus sp. can last a long time. The study aimed to determine the effect of the Bacillus sp. endophytic bacteria formulated with some waste and get the best formulation towards paddy. The research has been conducted in isolation room in industrial business unit Biofertilizer and Biopesticides and the Experimental Farm of Agriculture Faculty, University of Riau, in November 2015 until March 2016. The research was conducted experimentall using on completely randomized design (CDR) with 5 treatments and 4 replications. The data were analyzed statistically by analysis of variance and tested further with Duncan's multiple range test at 5% level. The results showed that giving Bacillus sp. bacteria formulated with sago waste is a formulation which tends best as it can increase the number of tillers total, the percentage of productive tiller, weight of 100 grain pithy, dry grain per panicle and the percentage of grain pithy. Keywords: Endophytic Bacillus sp., formulation, waste, Oryza sativa L.